Disaggregating the Developing Welfare State: Provincial Social Policy Regimes in China. (October 2017) - Ratigan, Kerry
Highlights: Chinese provinces diverge systematically in their social policy priorities. Some provinces emphasize education, while others prioritize poverty alleviation. This divergence is only partially explained by provincial wealth and needs. Provinces with an export-oriented development strategy tend to prioritize education. Provinces with greater unrest emphasize poverty alleviation to foster political stability. Summary: Local variation in social welfare provision appears in myriad contexts around the world. And yet, our attempts at conceptualizing welfare regimes focus on the national level. In China, local authorities have shaped social policy implementation since economic reforms. In this paper, I answer three questions about subnational variation in social policy provision in China: (1) Have Chinese provinces diverged in their social policy provision?; (2) How do provincial social policy regimes differ from one another?; (3) What explains variation in provincial social policy spending? To answer the first question, I conduct a cluster analysis of provincial social policy spending data. I find that provinces systematically diverge in their social policy priorities. While some provinces invest in education to develop human capital and promote economic growth, others emphasize poverty alleviation. I propose a typology to conceptualize these tendencies. I then test for these divergent approaches using between-effects regression models of provincial social policy spending. Although provincial wealth and needs sometimes play a role in allocations for social policy, I find that economic development strategy and social instability are associated with distinct approaches to social welfare spending. These distinct provincial welfare regimes have implications for the adoption, implementation, and ultimately, effectiveness of social policy in China.